Reproductive development of “amancay” Ismene amancaes (Amaryllidaceae) in its natural environment - Suni, Mery L. (2011)
Ismene amancaes “amancay” is a bulbose species typical of the central coast vegetation of Peru called “lomas”. This species sprouts in June during the beginning of the winter-fog period. It has large yellow, aromatic flowers valued for their ornamental value. Our goal was to examine the reproductive development of Ismene amancaes in its natural environment, and we recorded monthly observations during a yearlong study. Observations of the interior of the bulbs allowed recording of the beginning of floral bud formation and development, relating them to leaf formation and edaphic humidity. We found that the first floral buds develop the year before their emergence in December, reaching a maximum number of floral buds in February, during the Summer. Floral bud differentiation starts after leaves that will emerge the following year have developed. This occurs during a period of maximum decrease in edaphic humidity and an increase in air temperature (November). The inflorescence is the only branching that develops while the apical bud continues developing leaves. In June, the small inflorescence reaches the neck of the bulb and surpasses it followed by those leaves developed before the inflorescence that surround both the inflorescence and the apical foliar bud. The foliar bud will continue its development, and in July two of the leaves expand, while the smaller ones remain inside the bulb until the following year’s Lomas season. It can be noted that the reproductive success of Ismene amancaes in its initial development depends on the photoreserves accumulated in the bulb the previous growth period.